การใช้ประโยชน์จากแป้งเหลือทิ้งระหว่างการผลิตเส้นก๋วยเตี๋ยวเพื่อการผลิตฟิล์มแป้ง - ชนิดา นวลคำ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This research has investigated the possibility of producing flour films based on waste flour during noodle production. The films from the waste flour were prepared by casting method. The results showed that at waste flour solution concentration of 75 % w/v, and total plasticizer (glycerol and sorbitol) concentration of 40 % w/w (based on dry weight of waste flour) with various glycerol/sorbitol ratios as 2:1, 3:1 and 4:1 could produce the flour films properly. Increasing the glycerol content resulted in decreased values of tensile strength and elongation at break and increased values of solubility in water and water vapor transmission rate of films. The films prepared from the waste flour solution and plasticizer concentration above with glycerol/sorbitol ratios as 2:1, 3:1 and 4:1 had average values of the tensile strength: 2.16, 1.33 and 1.26 MPa, respectively, the elongation at break: 69.27, 55.61 and 54.79%, respectively, the solubility in water: 26.95, 30.84 and 31.19%, respectively, and the water vapor transmission rate: 2834.56, 3226.29 and 3233.30 g•m-2•day-1, respectively. The changes in equilibrium moisture content of films produced from waste flour solution concentration of 75 % w/v, total plasticizer (glycerol and sorbitol) concentration of 40 % w/w (based on dry weight of waste flour) with various glycerol/sorbitol ratios as 2:1, 3:1 and 4:1 under temperature conditions of 5, 25 and 45 C and in the water activity values of 0.11, 0.23, 0.32, 0.44, 0.58, 0.75, 0.84 and 0.90 followed by Henderson’s equation which gave higher adjusted coefficient of determination (R2adj) and lower root mean squares error (RMSE). The changes in physical and mechanical properties of films (used waste flour solution concentration of 75 % w/v, total plasticizer (glycerol and sorbitol) concentration of 40 % w/w (based on dry weight of waste flour) with various glycerol/sorbitol ratios as 2:1, 3:1 and 4:1) kept at the temperature of 5, 25 and 45 C and relative humidity (RH) 58 % for 30 days revealed that for all glycerol/sorbitol ratios the values of L* , a* , b* and total color difference (ΔE*) decreased at the temperatures of 5 and 25 C. When these films were kept at temperature of 45 C, the values of b* and total color difference (ΔE*) increased while the values of the water vapor transmission rate, tensile strength and elongation at break of films significantly decreased (p<0.05) during storage period. Application of films (waste flour solution concentration of 75 % w/v, total plasticizer (glycerol and sorbitol) concentration of 40 % w/w (based on dry weight of waste flour) with glycerol/sorbitol ratios as 2:1) was investigated by adding various potassium sorbate concentrations (10, 20 and 30 % w/v). It was found that the films with the addition of potassium sorbate concentration of 20 %w/v gave the highest average value of the elongation at break (73.01%) and then the films were applied on fresh strawberries wrapping for investing their quality. The fresh strawberries put on foam trays were covered with the flour films and kept at temperature of 5 C and relative humidity (RH) 90 % for 9 days. The results found that the fresh strawberries covered with the films prepared above had average values of phenol compounds content, antioxidant content and firmness of 326.12 milligrams of Gallic acid equivalents (GAE) per 100 gram of fresh strawberry, 2.66 milligrams Trolox equivalent (TE) per gram of fresh strawberry and 0.27 N, respectively. These average values were greater than these of fresh strawberries covered with the films without the addition of potassium sorbate and also without film covering, respectively. In addition, total plate count (log cfu/g) of these strawberries covered with the films containing this potassium sorbate concentration of 20 % w/v was lower as well.